PEMANFAATAN HASIL HUTAN BUKAN KAYU SEBAGAI BAHAN INSEKTISIDA ALAMI - Cahyana, Budi Tri; Arhamsyah, Arhamsyah (Kementerian Perindustrian, 2012)
Non-timber forest products (NTFPs) such as the root of Akar Wangi (Vetiveria zizainoides), Durianâs bark (Durio zibethinus Murr), Jaringau (Acorus Calamus L.), Liligundi (Vitex trifolia), Gemor bark (Alseodaphne spp.), Â and Neem seeds (Azadirachta indica A. Juss.) have good potential as a natural insecticide. They can be usedÂ for anti-mosquito materials that can be prevent the development of vector-borne Dengue Haemorrhagic Fever (DHF). Disruptive effects of the plants to the insects come from the odor which produces from the plant. Judging from the compounds that contained in non-timber forest products (NTFPs), beside used as anti-mosquito repellent, it can also used Â as other pests repellant such as bugs,Â Â termites, ants, etc. The end product also can be diversedÂ as insect repellent burns, topical / lotion, spray, and others.Keywords : Â akar wangi, Â durian bark, jariangau, liligundi, gemor bark, mimba, natural insecticide